ANALYSIS OF PROFITABILITY AND DIVIDEND POLICY ON THE VALUE OF PT INDOFOOD SUKSES MAKMUR LISTED ON THE INDONESIAN STOCK EXCHANGE FOR THE PERIOD 2021-2024 - Muh. Haekal Yunus; Nurfatimah Azzahra Baso; Elisa Pamuso; Icha Pakinja; Munawir Munawir (Jurnal Mahasiswa Manajemen, 2025)
This study aims to analyze the effect of profitability and dividend policy on company value at PT Indofood Sukses Makmur Tbk, listed on the Indonesia Stock Exchange for the period 2021-2024. The research method used is quantitative descriptive analysis with secondary data obtained from annual financial reports and company stock price data. The data is analyzed through the calculation of profitability and dividend policy financial ratios and testing their influence on company value. The results of the study indicate that dividend policy and profitability, both partially and simultaneously, have a significant effect on company value. However, there is a tendency that an increase in profitability is not always followed by an increase in company value if it is not accompanied by an optimal dividend policy. These findings provide important considerations for investors and company management in determining dividend policy strategies and investment decisions in the future.